2019
DOI: 10.1002/nbm.4075
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent changes in metabolite profile and lipid saturation in dystrophic mice

Abstract: Duchenne Muscular Dystrophy (DMD) is a fatal X-linked genetic disorder. In DMD, the absence of the dystrophin protein causes decreased sarcolemmal integrity resulting in progressive replacement of muscle with fibrofatty tissue. The effects of lacking dystrophin on muscle and systemic metabolism are still unclear. Therefore, to determine the impact of the absence of dystrophin on metabolism, we investigated the metabolic and lipid profile at two different, well-defined stages of muscle damage and stabilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…However, our investigation is in agreement with earlier reports in support of lipids and particularly of cholesterol metabolism abnormalities in DMD 13,14,[106][107][108][109][110][111][112]15,20,[100][101][102][103][104][105] . Of particular interest, Steen and colleagues reported the improved dystrophic parameters in an mdx mouse that overexpress the NPC1 gene, an accelerator of intracellular cholesterol trafficking 113 , while Milad and colleagues reported the correlation between increased plasma cholesterol and accentuated muscular dystrophy in the mdx mouse 112 , which together supporting that perturbation of cholesterol metabolism affects the DMD phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…However, our investigation is in agreement with earlier reports in support of lipids and particularly of cholesterol metabolism abnormalities in DMD 13,14,[106][107][108][109][110][111][112]15,20,[100][101][102][103][104][105] . Of particular interest, Steen and colleagues reported the improved dystrophic parameters in an mdx mouse that overexpress the NPC1 gene, an accelerator of intracellular cholesterol trafficking 113 , while Milad and colleagues reported the correlation between increased plasma cholesterol and accentuated muscular dystrophy in the mdx mouse 112 , which together supporting that perturbation of cholesterol metabolism affects the DMD phenotype.…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, we found that the content of C18:2 associated with TAGs was significantly increased. The unsaturation index in the lipids showed a decreased trend in gastrocnemius muscle from 6‐week‐old MDX mice but increases more quickly in 24‐week‐old MDX mice vs. controls 58 . We found that ectopic adipose tissue induced by GLY injection significantly decreased the percentages of SFAs and MUFAs, while it significantly increased PUFAs in muscle.…”
Section: Discussionmentioning
confidence: 60%
“…To that end, untargeted metabolomics and comparative transcriptomics data are increasingly being used as the basis for building metabolic models that describe the physiological state of a cell [4][5][6]. Examples of this approach can be found in disciplines ranging from mammalian genetic disorders and cancer biology, to antibiotic modes of action and pathogen-host interaction [7][8][9][10]. While these analyses can contribute to defining the response to various cellular perturbations [11,12], they are most significant when confirmed by rigorous genetic, biochemical, and molecular biological experimentation.…”
Section: Introductionmentioning
confidence: 99%